Communists and perverts under the palms : the Johns Committee in Florida, 1956-1965 - Braukman, Stacy Lorraine (University Press of Florida, 2012)
In 1956, state Senator Charley Johns was appointed the chairman of the newly formed Florida Legislative Investigation Committee, now remembered as the Johns Committee. This group was charged with the task of unearthing communist tendencies, homosexual persuasions, and anything they saw as subversive behavior in academic institutions throughout Florida. With the cooperation of law enforcement, the committee interrogated and spied on countless individuals, including civil rights activists, college students, public school teachers, and university faculty and administrators. Today, the actions.